'The press has gone crazy': online media and political rhetoric of immigrants in the USA. (27th April 2023) - Mills, Jack M.; Gomes, Silvia; Walzak, Jessica
Over recent decades, accessibility of mass media has introduced a new arena for the dissemination of political rhetoric to the public, and politicians have capitalised on the capacity for mass media to polarise public opinion on contested social issues. Research has argued that President Trump has extended prior rhetoric on the dangers of illegal immigration to also encompass asylum seekers and other immigrants entering the USA legally in order to solidify political support from citizens fearful or resentful of these minority groups. Through a content analysis of online news articles collected from FOX, CNN, and CBS between 2017-2019, we explore the media representations of immigration, particularly regarding those crossing the USA-Mexico border. Although each media outlet has a particular way of portraying this social and political issue, overall findings illustrate increases to the frequency of news media narratives criminalising refugees crossing the southern border, exacerbating political divides on immigration issues, and garnering support for restrictive, conservative-led anti-immigration policies.